Analisis Faktor-Faktor Yang Berpengaruh Terhadap Kinerja Balai Besar Pengawas Obat Dan Makanan Di Yogyakarta Dalam Menangani Kasus Makanan Bermelamin: Analysis of Factors Affecting Performance of National Agency of Drug and Food In Yogyakarta In Handling Melamine Containing Food Cases - Khusnul Diana (Universitas Tadulako, 2017)
Melamine is not prohibited chemical to mix into food product. Around 2008, Melamine had found in baby milk which was made by China to make high protein level. To see BBPOM Yogyakarta’s performance handling of food which has contaminated of melamine, it is needed evaluation from customer’s satisfaction and affection of monitoring food contaminated melamine’s factors. In addition, it is necessary to know the gap between expectation and society’s perception. The study is descriptive explorative research. The study has done by giving performance questionnaire and the factor that affect to performance of employee at Investigation and Inspection sector in BBPOM Yogyakarta and qualitative analysis has done by interview. Based on the analysis result, personal/human resources, monitored system and infrastructure factors has not significance effect to BBPOM Yogyakarta performance handling contaminated food, because the monitoring has limited for withdrawing and scrapping product. From the interview result is known that there is an effect between personal/human resources, monitored system and infrastructures factors, because it is influenced by theoretical and subjectivity of respondent.